Front Cover Picture: An Efficient Route to Isochromene Derivatives via Cascade Radical Cyclization and Radical‐Radical Coupling (Adv. Synth. Catal. 18/2019). Issue 18 (31st July 2019) - Yu, Kaili; Li, Minyan; Deng, Guogang; Liu, Chunxiang; Wang, Jing; Liu, Zhengfen; Zhang, Hongbin; Yang, Xiaodong; Walsh, Patrick J.
Abstract : The front cover picture, designed by Xiaodong Yang, Patrick J. Walsh and co‐workers, illustrates a novel and efficient route to construct isochromene derivatives through a cascade radical cyclization strategy. Aryl radicals derived from SET between 2‐azaallyl anions and 2‐iodobenzyl allenyl ethers trigger a radical cyclization to construct the isochromene core with formation of an allylic radical. The allylic radical then undergoes coupling with the azaallyl radical to give the products in good to excellent yields. Details of this work can be found in the Update on pages 4354–4359 (K. Yu, M. Li, G. Deng, C. Liu, J. Wang, Z. Liu, H. Zhang, X. Yang, P. J. Walsh, Adv. Synth. Catal . 2019, 361, 4354–4359; DOI: 10.1002/adsc.201900497 ).